Pengaruh Karakteristik Perusahaan dan Struktur Kepemilikan Terhadap Manajemen Laba - Ardian, Alvin; Dewi, Novy Silvia (Jurnal Ilmiah Wahana Pendidikan, 2023)
The earnings performance of the issuer becomes an important indicator for the capital market due to being able to predict the earning power of the company ahead in order to obtain an increase in the price of the stock. Thus, the company’s owners aim to test and suppress management’s commitment to accountability for better financial outcomes in the future. As a result, management works hard to satisfy shareholders even in a cunning way. Earning management becomes the main action of the management in satisfying stakeholders, resulting in a conflict of interest between the management and the owner which leads to agency costs. Analysts found that bonus compensation in the form of stock ownership options was able to influence firm manager behavior of earning management. Likewise, with the age and profitability of the company increasingly avoiding earning management activities. Earning management activities can be eroded through the presence of additional roles including independent board of commissioners, managerial, and institutional ownership. The research objectives describe the impact of company characteristics and ownership structures on earning management on infrastructure, utility, and transport subsector companies listed in the IDX during 2018-2021. The results of the observations showed new findings, including the proportion of independent commissioners, managerial ownership, and institutional influences significant positively on earning management.